Metodologi dan Pemikiran Shaykh Mustafa Abdul Rahman: Kajian Terhadap Tafsir al-Quran al-Hakim Juzu' Satu - Ismail, M. F.; Yusof, N. H.; Wan Abdullah, W. R. (Universiti Sains Islam Malaysia, 2024)
The work of interpretation on the Malay Archipelago, especially in the Malay Land in the early 20th century was greatly influenced by the reformation of Islam in Middle East, triggered by Syaykh Muhammad Abduh (1849-1905). The works of the reformists have insired many Islah scholars, especially in the study of interpretations. This article discusses how far the methodology and thinking of a local interpretation scholar, Syaykh Mustafa Abdul Rahman Mahmud (1918-1968) have contributed to the interpretation of Tafsir al-Quran al-Hakim, focusing on the first volume. Therefore, this research has found that Syaykh Mustafa Abdul Rahman Mahmud methodology and thinking culture in the first volume of the Tafsir al-Quran al-Hakim was influenced by the innovation flow, adopting the Tafsir al-Manar and Tafsir al-Maraghi as reference and guide.